ANALISIS DAMPAK SOSIAL EKONOMI MASYARAKAT DALAM PERSPEKTIF KEBIJAKAN PEMERINTAH DAERAH: (Studi Pada Ritel Alfamart Dan Indomaret Di Kecamatan Selebar Kota Bengkulu) - Noviyanto, Hernowo; Darmawi, Edi; Caniago, Afifah Mardiyah (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2022)
In research that uses qualitative research methods with the type of non-participatory observation, research that investigates the activities of small business actors, traditional grocery figures and consumers. Data collection to obtain information, researchers conducted by interviewing related parties such as the public or consumers, traditional grocery store traders, and employees of Alfamart and Indomaret. The results of this study indicate that the rampant development of Alfamart and Indomaret has a social and economic impact on traditional grocery store small businesses. From a social perspective, there are changes in the way of life and culture that develop in the community. In addition, from an economic point of view, it has an impact on decreasing income as well as unhealthy economic activities for small traders in traditional grocery stores.